Omnidirectional, Broadband Light Absorption in a Hierarchical Nanoturf Membrane for an Advanced Solar-Vapor Generator - Kim, Jong Uk; Kang, Seung Ji; Lee, Sori; Ok, Jehyung; Kim, Yongjae; Roh, Seung Hun; Hong, Haeleen; Kim, Jung Kyu; Chae, Heeyeop; Kwon, Seok Joon; Kim, Tae-il (WILEY-V C H VERLAG GMBH, 2020)
Solar-thermal materials have been intensively studied in the context of production and localization of thermal energy, targeting an industry level application. Although photonic and optical strategies for enhancing light absorption have increased the efficiency of photo excitation/conversion into thermal energy, most of them have several limitations such as large area fabrication, thermal stability and broadband/omnidirectional light absorption. In this study, a gold-coated hierarchical nanoturf membrane (Au/h-Nanoturf membrane) incorporated with randomly distributed high aspect ratio (AR) nanostructures and micro-through holes is proposed. The Au/h-Nanoturf has peculiar black structures that provide advantages in forming a membrane with a large area and in absorbing broadband solar light spectrum. Furthermore, the membrane is combined with micro-cone array which makes it exhibit exceptionally omnidirectional light absorption properties. Using computational analysis, it is confirmed that the micro-cone array substantially contributes to the omnidirectional solar absorption irrespective of the wavelength. The optimized structural parameters for the maximum efficiency of the solar-thermal materials are also found. The prepared solar-vapor generator with the optimized structural features exhibits 91% average conversion efficiency under one sun condition. The efficiency is sustainable for up to four weeks. The highly efficient and omnidirectional broadband-absorbing solar-thermal membrane can be readily employed, targeting an industry level application.
Keywords: STEAM-GENERATION; EFFICIENT; GRAPHENE; ABSORBER; ANTIREFLECTION; OXYGEN; HEAT